EUS-guided gastroenterostomy versus surgical gastroenterostomy for the management of gastric outlet obstruction: a systematic review and meta-analysis - Kumar, Anand; Chandan, Saurabh; Mohan, Babu P.; Atla, Pradeep R.; McCabe, Evin J.; Robbins, David H.; Trindade, Arvind J.; Benias, Petros C. (Endoscopy International Open, 2022)
Background and study aims Surgical gastroenterostomy (SGE) has been the mainstay treatment for gastric outlet obstruction (GOO). The emergence of endoscopic ultrasound-guided gastroenterostomy (EUS-GE) presents a less invasive alternative for palliation of GOO. We conducted a comprehensive review and meta-analysis to compare the effectiveness and safety of EUS-GE compared to SGE.Methods Multiple electronic databases and conference proceedings up to April 2021 were searched to identify studies that reported on safety and effectiveness of EUS-GE in comparison to SGE. Pooled odds ratios (ORs) of technical success, clinical success, adverse events (AE) and recurrence, and pooled standardized mean difference (SMD) of procedure time and post-procedure length of stay (LOS) were calculated. Study heterogeneity was assessed using I2 and Cochran Q statistics.Results Seven studies including 625 patients (372 EUS-GE and 253 SGE) were included. EUS-GE had lower pooled odds of technical success compared with SGE (OR 0.19, 95 % confidence interval [CI] 0.06–0.60, I2 0 %). Among the technically successful cases, EUS-GE was superior in terms of clinical success (OR 4.73, 95 % CI 1.83–12.25, I2 18 %), lower overall AE (OR 0.20, 95 % CI 0.10–0.37, I2 39 %), and shorter procedure time (SMD –2.4, 95 % CI –4.1, –0.75, I2 95 %) and post-procedure LOS (SMD –0.49, 95 % CI –0.94, –0.03, I2 78%). Rates of severe AE (0.89, 95 % CI 0.11–7.36, I2 67 %) and recurrence (OR 0.49, 95 % CI 0.18–1.38, I2 49 %) were comparable. Conclusions Our results suggest EUS-GE is a promising alternative to SGE due to its superior clinical success, overall safety, and efficiency. With further evolution EUS-GE could become the intervention of choice in GOO.